Better Prevention of COVID-19 and Infectious Diseases in Islamic Culture: A Study of Islam and Health - Mir Rumi Mustafizur Rahman; Md. Abdul Qader; Mokter Hossain (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
This manuscript aims at delineating the significance of Islamism in health science, especially in the contemporary pandemic of COVID-19. The first and foremost objective of this research work is to find out that the daily practice of Islam is better prevention for the people to be exempted from the diseases that occurred by COVID-19 and other disease-bearing viruses. It also observes that the daily activities in the Islamic religion always keep a man clean and danger-free from coronaviruses that have become a triumphant spirit on the medical science and technology in this digital world. This article is also eager to investigate and accumulate the Islamists' regular practices which act for them as the medicine of their viral diseases like COVID-19. The research work is done by the qualitative method. To make this research authentic, information has been collected from different primary and secondary sources: the holy Quran, Hadith, Islamic books, articles from newspapers, journals, etc. Here in the manuscript, the authors have desired to make a result that people should not avoid and ignore Islamism which can keep all human beings lucid, clean, and free from viral diseases, especially COVID-19. Finally, the study gives some recommendations on Islam which is scientifically and logically proven and considered the best religion for keeping health safe and sound in the viral diseases of the contaminated world.